Pertumbuhan Ayam Kampung Super Umur 3-10 Minggu Yang Diberikan Eco-Enzyme Dalam Campuran Air Minum - Frederikus Armando Jerubu; Ni Ketut Etty Suwitari; I Gusti Ayu Dewi Seri Rejeki (Fakultas Pertanian, Universitas Warmadewa, 2026)
The high cost of feed and the demand for increased production efficiency in the super village chicken farming business encourages the need for innovation in the use of environmentally friendly natural materials. Ecoenzymes, as a result of organic waste fermentation, have the potential to support digestive health and nutrient utilization so that they are expected to improve the growth performance of super village chickens. This study aims to determine how the provision of eco-enzymes in drinking water mixtures affects the growth of super village chickens aged 3-10 weeks and To determine at what level the provision of eco-enzymes in drinking water mixtures affects the growth of super village chickens aged 3-10 weeks. The design used in this study was a Completely Randomized Design (CRD) consisting of 5 treatments and 3 replications. The treatments used were E0 = Chickens without eco-enzyme in the drinking water mixture, E1 = Chickens given eco-enzyme in 20 ml of drinking water mixture, E2 = Chickens given eco-enzyme in 40 ml of drinking water mixture, E3 = Chickens given eco-enzyme in 60 ml of drinking water mixture and E4 = Chickens given eco-enzyme in 80 ml of drinking water mixture. The results showed that the provision of eco-enzyme in the drinking water mixture had no significant effect (P>0.05) on the initial body weight, weight gain, final body weight, ration consumption, and FCR value of super kampung chickens. However, the provision of eco-enzyme had a very significant effect (P<0.01) on drinking water consumption. Although statistically insignificant, there was a tendency for increased body weight gain and feed efficiency in treatments E3 and E4. It was concluded that the provision of eco-enzyme up to 80 ml in drinking water has not been able to significantly improve the growth performance of super kampung chickens at the age of 3–10 weeks.